2010
DOI: 10.1590/s0103-84782010005000038
|View full text |Cite
|
Sign up to set email alerts
|

Falhas na utilização de poliacetal e poliamida em forma de haste intramedular bloqueada para imobilização de fratura femural induzida em bovinos jovens

Abstract: Apesar da expressiva evolução da ortopedia veterinária nos últimos anos, as fraturas de ossos longos em grandes animais são constante desafio para o médico-veterinário. O presente estudo é parte da proposta de desenvolvimento de um sistema de haste intramedular polimérica, de baixo custo e fácil aplicação, para uso em bovinos jovens e neonatos. Os objetivos foram avaliar, in vivo, hastes de poliacetal e poliamida para imobilização de fraturas femorais em bovinos jovens. Cinco bezerros machos foram submetidos à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
(10 reference statements)
1
11
0
4
Order By: Relevance
“…Due to its anisotropy, when flexed the fault, it will always be present on the side subjected to the traction (SPADETO JUNIOR et al, 2010). In this study, crack nucleation (bone-rod) was observed on the area tractioned, as the bone is less resistant to traction than compression.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Due to its anisotropy, when flexed the fault, it will always be present on the side subjected to the traction (SPADETO JUNIOR et al, 2010). In this study, crack nucleation (bone-rod) was observed on the area tractioned, as the bone is less resistant to traction than compression.…”
Section: Resultsmentioning
confidence: 65%
“…In this study, crack nucleation (bone-rod) was observed on the area tractioned, as the bone is less resistant to traction than compression. Similarly, SPADETO JUNIOR et al (2010), in a study (in vivo) that used polyamide for the stabilization of induced fractures in the femurs of calves, have reported that half of the inserted rods had a fracture on the interface containing the screws close to the osteotomy line. In the present study; however, the rupture was observed in the region of the osteotomy and not by the screws.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Por apresentar melhor comportamento à flexão em relação ao polipropileno e ao poliacetal, a poliamida, que também possui maior módulo de resistência à flexão e maior tensão de ruptura à compressão, poderia ser considerada o material com maior chance de promover imobilização eficiente em um estudo in vivo. Analisando um estudo similar in vivo previamente publicado (SPADETO JUNIOR et al, 2010), observa-se concordância nos resultados, pois nesse estudo houve fratura em seis de sete hastes de poliacetal implantadas e em duas de quatro hastes de poliamida implantadas em fraturas diafiseais em bezerros, com 85 a 100 dias de idade. Coincidentemente, nesse mesmo estudo, todas as fraturas de hastes ocorreram na interface com os parafusos mais próximos à linha de fratura.…”
Section: Resultsunclassified
“…The use of polymeric intramedullary interlocking nails in a young calf fracture model has been considered . Initial studies demonstrated clinical healing in humeral fractures fixed with intramedullary polypropylene nails, indicating their potential for clinical use; however, polyacetal and polyamide nails failed when used to fix femoral fracture in the same model .…”
mentioning
confidence: 99%